2020
DOI: 10.1016/j.jpain.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Endogenous Pain Modulation With Aging: A Meta-Analysis of Temporal Summation and Conditioned Pain Modulation

Abstract: The purpose of this article was to examine age-related changes in conditioned pain modulation (CPM) and temporal summation (TS) of pain using meta-analytic techniques. Five electronic databases were searched for studies, which compared measures of CPM and TS among healthy, chronic pain-free younger, middle-aged, and older adults. Eleven studies were included in the final review for TS and 11 studies were included in the review of CPM. The results suggested a moderate magnitude of difference in TS among younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 45 publications
(119 reference statements)
4
36
0
Order By: Relevance
“…In the current study there were only six participants (four women) above 40 years, which explains the limited influence of age. This is in line with the literature (Grashorn et al., 2013; Hackett et al., 2020; Lariviere et al., 2007; Leone & Truini, 2019). Gender influenced only the CPM‐efficacy at the m. quadriceps with all the conditioning stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study there were only six participants (four women) above 40 years, which explains the limited influence of age. This is in line with the literature (Grashorn et al., 2013; Hackett et al., 2020; Lariviere et al., 2007; Leone & Truini, 2019). Gender influenced only the CPM‐efficacy at the m. quadriceps with all the conditioning stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the late CPM-effect, i.e., endogenous inhibition lasting for at least 5 min after CS termination, was smaller than the early CPM-effect during CS application, in line with previous studies. The magnitude of the early CPM-effect induced by heat as TS was similar to our previous reliability study [10], though the range in the existing literature is quite high and depends also on the subjects' age [41]. Interestingly, the pain reduction induced by PCES as TS in the current study was lower compared to our previous two studies, which was also paralleled by smaller changes of the N1-P1 amplitudes of the PCES-evoked potentials [20,36] A study demonstrated that the CPM-effect depends on the perceived level of the CS pain when it is altered by cognitive manipulation, rather than solely on its physical intensity [42].…”
Section: Extend and Duration Of The Cpm-effectsupporting
confidence: 85%
“…Our models were not able to find a relationship between intracortical excitability and quantitative sensory testing measurements (CPM and pain thresholds). This is one of the most powered studies to analyze this relationship in a multivariate model adjusting for clinical factors that influence both markers, such as age 20 , 51 , gender 52 , emotion 53 , and cognitive variables 54 . However, the relationship between the CPM and cortical excitability is not well understood.…”
Section: Discussionmentioning
confidence: 99%